A generalizable strategy for crosslinkable albumin-based hydrogels and application as potential anti-tumor nanoplatform. (May 2023) - Lv, WanWan; Yang, Kai; Yu, Jingwen; Wu, Yiqing; Zhang, Mengdi; Liu, Zichuan; Wang, Xixuan; Zhou, Jiahui; Ma, Haoran; Yi, Rongyuan; Chu, Hui; Chen, Jian
Albumin-based hydrogels have emerged as promising nanoparticle systems for the effective delivery of hydrophobic anticancer drugs. Anti-cancer drugs often cause some adverse effects, such as toxicity and rapid clearance by mononuclear phagocytic systems. Herein, a new strategy of synthesizing N-hydroxysuccinimide (NHS)-activated linker to form crosslinkable albumin-based hydrogels (CABH) is reported. The CABH favored physiochemical characteristics improvement of doxorubicin (Dox) and drug release. The CABH was constructed depending on the crosslinking reaction between NHS activated glycerol and albumin. The size of CABH was approximately 200 nm examined by dynamic light scattering (DLS) and transmission electron microscopy (TEM). It was found that the particle size and size distribution of the CABH remained stable in neutral PBS for 1 week. Dox loaded CABH would be controllably released in weak acidic environment verified by in vitro release and in vitro cell imaging. The Dox loaded hydrogel results in significant killing in the case of acidic culture medium. Our work provides a crosslinking method to formulate albumin nanoplatform and improve the size, stability, drug loading capacity and controlled release, which throws light on the potential application in drug delivery. Graphical Abstract